2021
DOI: 10.3390/ijms222413630
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Affects Adipogenic Differentiation by Regulating Autophagy and MAPK Activation in 3T3-L1 and C2C12 Cells

Abstract: Kirsten rat sarcoma 2 viral oncogene homolog (Kras) is a proto-oncogene that encodes the small GTPase transductor protein KRAS, which has previously been found to promote cytokine secretion, cell survival, and chemotaxis. However, its effects on preadipocyte differentiation and lipid accumulation are unclear. In this study, the effects of KRAS inhibition on proliferation, autophagy, and adipogenic differentiation as well as its potential mechanisms were analyzed in the 3T3-L1 and C2C12 cell lines. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…The RAS effector ERK has been shown to phosphorylate PPARγ at Ser112 and consequently suppress PPARγ transcriptional activity (Shao et al, 1998;Choi et al, 2015). Concurrently, inhibition of KRAS has also been shown to promote in vitro adipogenic differentiation in the 3T3-L1 and C2C12 preadipocyte cell lines (Yu et al, 2021). Alternatively, RAS can indirectly suppress PPARγ activity through TAZ, the main downstream effector protein of the Hippo pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The RAS effector ERK has been shown to phosphorylate PPARγ at Ser112 and consequently suppress PPARγ transcriptional activity (Shao et al, 1998;Choi et al, 2015). Concurrently, inhibition of KRAS has also been shown to promote in vitro adipogenic differentiation in the 3T3-L1 and C2C12 preadipocyte cell lines (Yu et al, 2021). Alternatively, RAS can indirectly suppress PPARγ activity through TAZ, the main downstream effector protein of the Hippo pathway.…”
Section: Discussionmentioning
confidence: 99%
“…al, reported that MYC and SREBP1 cooperate to regulate the expressions of fatty acid genes, such as SCD1 in a feed-forward transcriptional loop, contributing to lipogenesis for neoplastic growth [42] . Inhibition of KRAS decreases the expression of SCD1, thereby reducing cell growth and inducing autophagy in 3T3-L1 and C2C12 cells, indicating that KRAS expression leads to changes in lipid accumulation capacity [43] . Consistent with the results above, KRAS inhibition using S -trans,transfarnesylthiosalicylic acid (FTS) decreases the gene expression of SCD1 in a dose-dependent manner, indicating that KRAS suppression hampers the expressions of lipogenesis-associated genes [44] .…”
Section: Discussionmentioning
confidence: 99%
“…After lysis, the mixture was centrifuged at 16,000× g for 10 min to collect the protein-containing supernatant. Briefly, western blot experiments were performed as described previously [34]. The antibodies used in the study are shown in Supplementary Table S3.…”
Section: Protein Separation and Western Blot Analysismentioning
confidence: 99%